Wage cyclicality and labour market institutions - Jo\~ao Pereira; Raul Ramos; Pedro S. Martins (Global Labor Organization (GLO), 2024)
Do labour institutions influence how wages respond to the business cycle? Such responsiveness can then shape several economic outcomes, including unemployment. In this paper, we examine the role of two key labour market institutions - collective bargaining and temporary contracts - upon wage cyclicality. Our evidence is drawn from rich, 2002-2020 matched data from Portugal. We find that workers not covered by collective agreements exhibit much higher wage cyclicality, especially new hires, compared to covered workers. In contrast, workers under temporary contracts do not exhibit sizable differences in cyclicality compared to counterparts under permanent (open-ended) contracts. Our findings highlight a novel angle through which labour institutions influence the labour market and the economy.
Keywords: J31; J52; J64; 330; Real wages; Business cycles; Collective bargaining; Temporary contracts; Employment Law; Matched data